Mesospheric Mountain Wave Breaking and Oceanic Wave Signatures During DEEPWAVE - Taylor, M.; Pautet, D.; Fritts, David C.; Doyle, James D.; Eckermann, Stephen D.; Williams, Bifford P.; Kaifler, Bernd; Bossert, Katrina; Criddle, Neal R. (2015)
DEEPWAVE is an international program designed to quantify gravity wave (GW) dynamics and effects from the ground to the upper mesosphere in unprecedented detail utilizing a range of airborne and ground-based measurements. DEEPWAVE was based on the South Island, New Zealand, to provide access to well-documented, but little understood, New Zealand and Tasmania “hotspots” as identified in satellite stratospheric measurements. Deep orographic GWs over New Zealand were a primary target, but multiple flights were also conducted over the Southern Ocean and Tasman Sea to quantify deep GW arising from convection, jet streams, and frontal systems. This presentation highlights new airborne and ground-based results obtained using an Advanced OH Mesospheric Temperature Mapper (AMTM) which creates high-quality intensity and temperature maps of a broad spectrum of mesospheric GWs. Two AMTM’s were employed, one sited at the NIWA Observatory, Lauder (45°S), on the South Island, and one on the NSF GV Gulfstream aircraft which was supplemented by two side viewing IR OH imagers providing large field, ~900 km cross-track, GW maps. These instruments formed part of a comprehensive measurements capability including airborne Rayleigh and Na lidars, dropsondes, ground-based Rayleigh lidar, all-sky imagers and wind measurements. A total of 25 long duration (typically 7-8 hours) nighttime flights were conducted creating an exceptionally rich data set. Here we focus on two key initial findings (a) discovery of large amplitude, mesospheric mountain waves and their intermittent wave breaking signatures, and (b) first measurements of large-field open-ocean mesospheric GW and their near-identical stratospheric wave signatures using AIRS satellite and model forecasting data.